Response of a 50kW Organic Rankine Cycle System Subject to Influence of Evaporators - Lee, Yuh-Ren; Kuo, Chi-Ron; Liu, Chih-Hsi; Fu, Ben-Ran; Wang, Chi-Chuan (Energy procedia, 2014)
The variations of the evaporator on the system responses of a 50 kWe ORC system using R-245fa are investigated. The effect of exit superheat on the ORC system depends of the types of the evaporator. For the plate evaporator, an exit superheat less than 10°C may cause ORC system unstable due to liquid entrainment. For maintaining stable operation, the corresponding Jakob number of the plate heat evaporator must be above 0.07. On the other hand, no unstable oscillation of the ORC system is observed for an exit superheat of 0∼17°C when the shell-and-tube heat exchanger is used as the evaporator.